(untitled) (Reading, Mass, 1994)
This adaptation of the definitive Foley guide provides a more concise introduction to computer graphics. Explanations of key concepts have been expanded and further illustrated assuming less background knowledge on the part of the reader.
Keywords: Computer graphics,Đồ họa máy tính